Continuous and scalable manufacture of amphibious energy yarns and textiles - Gong, Wei; Hou, Chengyi; Zhou, Jie; Guo, Yinben; Zhang, Wei; Li, Yaogang; Zhang, Qinghong; Wang, Hongzhi (Nature communications, 2019)
Biomechanical energy harvesting textiles based on nanogenerators that convert mechanical energy into electricity have broad application prospects in next-generation wearable electronic devices. However, the difficult-to-weave structure, limited flexibility and stretchability, small device size and poor weatherability of conventional nanogenerator-based devices have largely hindered their real-world application. Here, we report a highly stretchable triboelectric yarn that involves unique structure design based on intrinsically elastic silicone rubber tubes and extrinsically elastic built-in stainless steel yarns. By using a modified melt-spinning method, we realize scalable-manufacture of the self-powered yarn. A hundred-meter-length triboelectric yarn is demonstrated, but not limited to this size. The triboelectric yarn shows a large working strain (200%) and promising output. Moreover, it has superior performance in liquid, therefore showing all-weather durability. We also show that the development of this energy yarn facilitates the manufacturing of large-area self-powered textiles and provide an attractive direction for the study of amphibious wearable technologies. Textiles that can convert mechanical energy into electricity are attractive for wearable electronic devices, but application is hindered by stability, flexibility, and stretchability. Here the authors report scalable fabrication for a stretchable triboelectric yarn that is operational under water.